Comparison of Modernity & Social Development between Baku & Tabriz Metropolitan Dwellers - ali esmaeili; abdolrahim asadollahi; alireza mohseni tabrizi (توسعه اجتماعی, 2017)
The study was aimed to comparing two metropolitans of Baku and Tabriz regarding social development and modernity during a year. The social theory of modernity approach of McClelland, Rogers and Hygiene was employed as theoretical framework. In descriptive method, about 876 urban dwellers that are 15 years of age and above was sampled via ratio sampling method from Baku of Azerbaijan Republic and Tabriz of Iran in 2015. The MSDQ item was obtained with Cronbach’s alpha r≥80 in validity. The findings stated to the significant different between two metropolitans in all scales. The most effective variable were authority on urban sphere and social belongings (B=.843 & .769) in Tabriz and in Baku were SES and gender (B=.819 & .721). Values and norms are accompanied to social matters which are fundamentals of development. Modernity and social development have to be in policy making in developing strategies in both metropolitans. About seven developmental recommends were suggested as the end.